2006
DOI: 10.1161/circulationaha.105.574087
|View full text |Cite
|
Sign up to set email alerts
|

Obesity as Compared With Physical Activity in Predicting Risk of Coronary Heart Disease in Women

Abstract: Background-The comparative importance of physical inactivity and obesity as predictors of coronary heart disease (CHD) risk remains unsettled. Methods and Results-We followed 88 393 women, 34 to 59 years of age, in the Nurses' Health Study from 1980 to 2000.These participants did not have cardiovascular disease and cancer at baseline. We documented 2358 incident major CHD events (including nonfatal myocardial infarction and fatal CHD) during 20 years of follow-up, including 889 cases of fatal CHD and 1469 case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
229
3
20

Year Published

2007
2007
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 377 publications
(262 citation statements)
references
References 19 publications
10
229
3
20
Order By: Relevance
“…Moreover, the CAD event rate of obese women not characterized by abdominal obesity was essentially similar to what was recorded among nonobese women with an elevated waist circumference. A longer follow-up of the Nurses' Health Study (20 years) yielded similar results (34). Finally, in the landmark international cross-sectional, casecontrol INTERHEART study, involving more than 27,000 individuals stratified on the basis of their BMI values and WHR, subjects in the top quintiles of WHR were characterized by an increased odds ratio of MI irrespective of the BMI category considered (35).…”
Section: Obesity and Cad Risk: Beyond Body Weightmentioning
confidence: 62%
“…Moreover, the CAD event rate of obese women not characterized by abdominal obesity was essentially similar to what was recorded among nonobese women with an elevated waist circumference. A longer follow-up of the Nurses' Health Study (20 years) yielded similar results (34). Finally, in the landmark international cross-sectional, casecontrol INTERHEART study, involving more than 27,000 individuals stratified on the basis of their BMI values and WHR, subjects in the top quintiles of WHR were characterized by an increased odds ratio of MI irrespective of the BMI category considered (35).…”
Section: Obesity and Cad Risk: Beyond Body Weightmentioning
confidence: 62%
“…11 In the United States (US), it has been shown that health care costs are inversely associated with PA, after adjustment for Body Mass Index (BMI), 12 and it is estimated that health care costs are $US300 per person per year less for regularly active than for sedentary adults. 13 As it is now well established that weightrelated health problems are ameliorated by regular PA 14 17 As 78.5% of the participants in that study were men, the cost savings for women are less clear. The aims of this study were therefore to quantify relationships between PA, BMI and Medicare costs in a cohort of midage Australian women and to estimate the potential population cost savings associated with increasing PA and decreasing BMI in sedentary women.…”
mentioning
confidence: 98%
“…11 In the United States (US), it has been shown that health care costs are inversely associated with PA, after adjustment for Body Mass Index (BMI), 12 and it is estimated that health care costs are $US300 per person per year less for regularly active than for sedentary adults. 13 As it is now well established that weightrelated health problems are ameliorated by regular PA 14 and increased levels of fitness, 15 it might be expected that health costs would be lower in physically active people, regardless of BMI. However, most studies in this area have reported separately on the costs of inactivity and overweight/obesity 16 and few have reported costs associated with the combined effects of these risk factors.…”
mentioning
confidence: 99%
“…Strategies to promote childhood physical activity are becoming a public health priority, 1,2 both because an active lifestyle has direct health benefits, [3][4][5][6] and because physical activity plays a role in preventing obesity. 7,8 Childhood activity patterns may be particularly important if they persist into adulthood.…”
mentioning
confidence: 99%